2010
DOI: 10.3762/bjnano.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible light photocatalysis through fast crystallization of zinc oxide nanorods

Abstract: SummaryHydrothermally grown ZnO nanorods have inherent crystalline defects primarily due to oxygen vacancies that enhance optical absorption in the visible spectrum, opening up possibilities for visible light photocatalysis. Comparison of photocatalytic activity of ZnO nanorods and nanoparticle films on a test contaminant methylene blue with visible light irradiation at 72 kilolux (klx) showed that ZnO nanorods are 12–24% more active than ZnO nanoparticulate films. This can be directly attributed to the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 31 publications
0
101
0
Order By: Relevance
“…8 Initially the glass substrates were cleaned subsequently in soap water, acetone, ethanol and de-ionized (DI) water in an ultrasonic water bath. A ZnO seed layer was then deposited on the cleaned glass substrates by spraying 10 ml of 5 mM aqueous solution of zinc acetate at 350 °C.…”
Section: Synthesis Of Zno Nrsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Initially the glass substrates were cleaned subsequently in soap water, acetone, ethanol and de-ionized (DI) water in an ultrasonic water bath. A ZnO seed layer was then deposited on the cleaned glass substrates by spraying 10 ml of 5 mM aqueous solution of zinc acetate at 350 °C.…”
Section: Synthesis Of Zno Nrsmentioning
confidence: 99%
“…In the presence of ZnO NRs, the photocatalytic degradation of MB was observed to occur at a faster rate resulting in almost 50% reduction in MB concentration in less than 40 minutes of visible light illumination. The enhancement in the photocatalytic activity of ZnO NRs under visible light irradiation is mainly due to the presence of the surface defects in the hydrothermally grown ZnO NRs, 8,28,29 which allows sub-bandgap absorption in the material, generating active e-h pairs by absorbing some part of the visible spectrum. 30,31 From the UV/Vis absorption spectra of ZnO NRs ( Fig.…”
Section: Photocatalytic Degradation Of Mb Using Au-zno Nrsmentioning
confidence: 99%
“…Microshape dependency shows that ZnO nanorods (NRs) have the best optical properties among nanoshells and nanoneedles [5]. In contrast, it has been also reported that enhanced surface defects play a crucial role in ZnO nanostructures when it is used as a visible light photocatalyst [6–9]. …”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis is a promising technology based on the interaction between light and solid semiconductor particles and is able to induced the oxidation process and produce highly oxidative species which, not only cause the damage and inactivate the organisms , but also destroy a large variety of chemical contaminants.…”
Section: Introductionmentioning
confidence: 99%